Airflow limitation and tongue microbiota in community-dwelling elderly individuals. Issue 2 (24th May 2021) - Takeshita, Toru; Matsumoto, Koichiro; Furuta, Michiko; Fukuyama, Satoru; Takeuchi, Kenji; Ogata, Hiroaki; Asakawa, Mikari; Kageyama, Shinya; Hata, Jun; Ninomiya, Toshiharu; Inoue, Hiromasa; Yamashita, Yoshihisa
Numerous oral indigenous microorganisms are constantly introduced into the stomach via the laryngopharynx, and a portion of these microorganisms irregularly reaches the lower airways and lungs. This study investigated the association between airflow limitation and the status of tongue microbiota, which is a primary source of ingested oral bacterial populations. The study population consisted of 484 community-dwelling adults aged 70–80 years inhabiting Hisayama town, Japan, who underwent a regular health examination including dental examination and spirometry test in 2016. The bacterial density and composition of their tongue microbiota were determined using a previously used 16S rRNA gene to understand their relationship with oral health conditions. The present cross-sectional study compared the tongue microbiota status between elderly individuals with airflow limitation and those with normal airflow. The total bacterial density of the tongue microbiota of individuals with airflow limitation was significantly higher than that of individuals with normal airflow. Logistic regression analysis demonstrated that a high-biomass tongue microbiota was significantly associated with airflow limitation after adjustment for smoking intensity and other covariates (adjusted OR 1.61, 95% CI 1.01–2.60). Of the predominant commensals, higher amounts of Prevotella melaninogenica and Actinomyces odontolyticus were associated with a higher prevalence of airflow limitation. These results indicate that increased bacterial burden in the tongue microbiota is associated with a higher prevalence of airflow limitation. Bacterial enrichment in the tongue microbiota is associated with airflow limitation characterising COPD in community-dwelling elderly adults https://bit.ly/36qMf6G